Hybridization and low genetic diversity in the endangered Alabama red‐bellied turtle (Pseudemys alabamensis). Issue 6 (3rd June 2022) - Moreno, Nickolas; Heaton, Andrew; Bruening, Kaylin; Milligan, Emma; Nelson, David; Glaberman, Scott; Chiari, Ylenia
Abstract: Pseudemys alabamensis is one of the most endangered freshwater turtle species in the United States due to its restricted geographic distribution in coastal Alabama and Mississippi. Populations of P. alabamensis are geographically isolated from one another by land and saltwater, which could act as barriers to gene flow. It is currently unknown how differentiated these populations are from one another and whether they have experienced reductions in population size. Previous work found morphological differences between Alabama and Mississippi populations, suggesting that they may be evolutionarily distinct. Other Pseudemys turtles such as P. concinna and P. floridana occur naturally within the same geographic area as P. alabamensis and are known to hybridize with each other. These more abundant species could threaten the unique genetic identity of P. alabamensis through introgression. In order to evaluate the endangered status of P. alabamensis and the level of hybridization with other species, we used mitochondrial and nuclear microsatellite markers to assess genetic variation within and among populations of P. alabamensis throughout its range and estimate admixture with co‐occurring Pseudemys species. In P. alabamensis, we found no variation in mitochondrial DNA and an excess of homozygosity in microsatellite data. Our results show genetic differentiation between Alabama and Mississippi populations of P. alabamensis, and low estimated breeding sizes and signs of inbreeding for two populations (Fowl River, Alabama and Biloxi, Mississippi). We also found evidence of admixture between P. alabamensis and P. concinna / P. floridana . Based on our results, P. alabamensis is highly endangered throughout its range and threatened by both low population sizes and hybridization. In order to improve the species' chances of survival, focus should be placed on habitat preservation, maintenance of genetic diversity within both the Mississippi and Alabama populations, and routine population‐monitoring activities such as nest surveillance and estimates of recruitment. Abstract : Pseudemys alabamensis is one of the most endangered freshwater turtle species in the United States. Populations of P. alabamensis are geographically isolated from one another by land and saltwater, which could act as barriers to gene flow, resulting in the evolution of unique populations. Other Pseudemys turtles such as P. concinna and P. floridana occur naturally within the same geographic area as P. alabamensis and are known to hybridize with each other. These more abundant species could threaten the unique genetic identity of P. alabamensis through introgression. We used mitochondrial and nuclear microsatellite markers to assess genetic variation within and among populations of P. alabamensis throughout its range and estimate admixture with co‐occurring Pseudemys species. We found that P. alabamensis is highly endangered throughout its range and threatened by both low population sizes and hybridization. Conservation measures must be developed to prevent further reduction and extinction of this endangered species.